(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research is a descriptive study that aims to determine the description of the level of sickle kick ability in pencaksilat sports in SMA Negeri 12 Makassar students. The population in this study were all extracurricular students totaling 45 students. The sample in this study was 20 male SMA Negeri 12 Makassar students selected by simple random sampling. Data collection techniques were obtained through tests and measurements of sickle kick data. The data analysis technique used is percentage and analysis. The research data obtained the percentage of data on the ability of sickle kick ability in pencaksilat sports in SMA Negeri 12 Makassar students from 20 students or (100%), the Excellent category as many as 2 students or (10.0%), the Good category as many as 4 students or (20.0%), the Fair category as many as 11 students or (55.0%), the less category as many as 3 students or (15.0%), and the category is very less as many as 0 students or (0%). Thus, it can be concluded that the percentage of the final data results of the sickle kick ability in pencaksilat sports in SMA Negeri 12 Makassar students is in the Fair category.